Competences of the Nursing Teacher in the Elaboration of the Didactic Planning - Mateo Crisóstomo, Yadira (2023)
Objective: Describe the level of professional skills to develop a didactic planning in nursing teachers of a public university in the state of Puebla and Tabasco. Methods: The study design was quantitative, cross-sectional, descriptive and comparative of two Higher Education Institutions. Sampling was for convenience, with a final sample of 20 undergraduate nursing professors; 10 from the state of Puebla and 10 from Tabasco. An ex profesa personal data certificate was used and an instrument was applied to assess the nursing teacher's competencies in didactic planning, with a total of 12 items. This instrument has two dimensions subdivided into knowledge and practical skills of the teacher. Main Results: It is shown that 40% of nursing teachers have a low level of competence and 30% are between a moderate and high level with respect to knowledge of didactic planning. Likewise, regarding practical skills, 65% are located at a low level of competence and only 15% present a high level of competence. Overall Conclusion: Didactic planning in nursing is essential to ensure that students receive a quality education and are prepared to face the challenges of the nursing field.